Características Del Comercio De Cacao A Nivel Intermediario En La Provincia De El Oro-Ecuador - Salomón Barrezueta-Unda; Eveligh Prado Carpio; Rodrigo Jimbo Sarmiento (European Scientific Journal, ESJ, 2017)
The present study is of an exploratory nature. It analyzed the internal cocoa market at formal intermediary level in the municipalities of Pasaje and Santa Rosa, in the province of El Oro. The objective of this study is to estimate the time involved in the business of buying and selling Dry cocoa from the intermediaries when compared to the total cocoa exported and traded locally in 2014. It determines the percentage share of the national and CCN51 cacao production sites in Pasaje and Santa Rosa. For this purpose, the entire population was surveyed by 48 traders registered under the area of these studies. Also, the following variables were considered: time of commercial activity, time of purchase, total export in 2014, participation based on the type of cocoa in the local market, and origin of purchases. The results show that ≥50% of the respondents had more than 10 years of experience in the activity, with a total export of 2.43% in 2014. The result is in favour of the CCN51 cocoa which represented 71% of the total marketed between the two municipalities. This, however, came from Casacay in Pasaje and the rural area of Santa Rosa. The remaining 29% of the national cacao was identified in Progreso alto in Pasaje and Bella María in Santa Rosa. Similar research was recommended so as to determine the real contribution of the national cocoa at the level of local intermediation.